THE KONSEP MANAJEMEN BIMBINGAN DAN KONSELING PADA JENJANG SMA - Heni Diyah Harnum; Uman Suherman AS; Ibrahim Al Hakim (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
This study aims to analyze the concept of guidance and counseling (GC) management at the senior high school level through a literature review approach. The study focuses on the implementation of guidance and counseling management functions, including planning, organizing, implementation, and evaluation of services. The research method employed is a literature review by examining five research articles published between 2020 and 2025, obtained through Google Scholar based on specific inclusion criteria. The data analysis technique was conducted narratively and systematically. The findings indicate that guidance and counseling management in senior high schools has generally been implemented quite well through the application of POAC functions (Planning, Organizing, Actuating, and Controlling), the use of clear organizational structures, and collaboration among school personnel. However, several challenges remain, such as the limited number of guidance and counseling teachers, weak integration of digital technology, and the suboptimal evaluation of service impacts on students’ development. Therefore, it is necessary to strengthen digital-based guidance and counseling management and improve the managerial competencies of guidance and counseling teachers to ensure that services become more effective and adaptive to contemporary developments.